Sesquiterpene Lactones from Artemisia Genus: Biological Activities and Methods of Analysis - Bianca Ivanescu; Anca Miron; Andreia Corciova (Journal of Analytical Methods in Chemistry)
Sesquiterpene lactones are a large group of natural compounds, found primarily in plants of Asteraceae family, with over 5000 structures reported to date. Within this family, genus Artemisia is very well represented, having approximately 500 species characterized by the presence of eudesmanolides and guaianolides, especially highly oxygenated ones, and rarely of germacranolides. Sesquiterpene lactones exhibit a wide range of biological activities, such as antitumor, anti-inflammatory, analgesic, antiulcer, antibacterial, antifungal, antiviral, antiparasitic, and insect deterrent. Many of the biological activities are attributed to the α-methylene-γ-lactone group in their molecule which reacts through a Michael-addition with free sulfhydryl or amino groups in proteins and alkylates them. Due to the fact that most sesquiterpene lactones are thermolabile, less volatile compounds, they present no specific chromophores in the molecule and are sensitive to acidic and basic mediums, and their identification and quantification represent a difficult task for the analyst. Another problematic aspect is represented by the complexity of vegetal samples, which may contain compounds that can interfere with the analysis. Therefore, this paper proposes an overview of the methods used for the identification and quantification of sesquiterpene lactones found in Artemisia genus, as well as the optimal conditions for their extraction and separation.